2013
DOI: 10.1080/10640266.2013.864891
|View full text |Cite
|
Sign up to set email alerts
|

Content Analysis of Male Participation in Pro-Eating Disorder Web Sites

Abstract: The pro-anorexia community has emerged as a powerful cultural movement that takes an at least partially positive attitude toward anorexia nervosa and other eating disorders. A systematic review of the literature on pro-ana forums focused specifically on females with eating disorders. However, epidemiological data suggest that as much as 25% of the eating disorders population is male. In our review of pro-anorexia web sites, we found a substantial number of participants were male. We conducted a qualitative con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…It did not focus on forums for nonmental health–related illnesses or discussions via social media. This review showed that studies focused primarily on a number of areas, including forums for specific diagnoses [7,8]; clinician-led or medical service–led sites, which are often used as an adjunct to other interventions [9-12]; and sites that focus on specific consumer groups including men and young people [13-15]. Analysis focused on 2 main areas: analyses of the content of forum posts and motivations and impact of forum use, but very little of this research focused on experiences from the forum user perspective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It did not focus on forums for nonmental health–related illnesses or discussions via social media. This review showed that studies focused primarily on a number of areas, including forums for specific diagnoses [7,8]; clinician-led or medical service–led sites, which are often used as an adjunct to other interventions [9-12]; and sites that focus on specific consumer groups including men and young people [13-15]. Analysis focused on 2 main areas: analyses of the content of forum posts and motivations and impact of forum use, but very little of this research focused on experiences from the forum user perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Other content-based research utilizes forums as a methodological tool to understand naturally occurring chat for groups that may be difficult to engage with through traditional research. In addition, 2 studies, for example, analyzed men’s mental health, including a study which focused on depression [15] and another on eating disorders [8].…”
Section: Introductionmentioning
confidence: 99%
“…These messages may be viewed positively: social support promoting self-efficacy across various age groups has been identified as important for exercise initiation and maintenance (Craggs, Corder, van Sluijs, & Griffin, 2011;Litt, Kleppinger, & Judge, 2002). Pro-eating disorder websites have similarly been found to be a source of social support and self-efficacy and provide a safe space in which individuals can interact with like-minded others (Borzekowski et al, 2010;Wooldridge, Mok, & Chiu, 2014). #Fitspiration text however, also facilitated a shared feeling of contempt towards those who did not belong or those who disapproved.…”
Section: "Nothing Tastes As Good As Skinny Feels")mentioning
confidence: 99%
“…Furthermore, many of the sites are interactive and offer forums through which participants can exchange stories or provide each other with support (Borzekowski and Rickert 2001;Mulveen and Hepworth 2006). This provision of support has been identified by members of pro-eating disorder online communities as one of the critical aspects of the groups (Brotsky and Giles 2007;Wooldridge et al 2014). In addition, however, participants report visiting pro-eating disorder websites to obtain help in maintaining disordered eating (Csipke and Horne 2007;Gavin et al 2008;Giles 2006), and the content of these sites often reaffirms the importance of thinness (Riley et al 2009).…”
Section: Pro-eating Disordersmentioning
confidence: 99%
“…Explorations of pro-eating disorder websites have conceptualized within a ''group identity'' framework, highlighting how these online groups develop a common identity, reinforced by the perceived hostility of the outgroup (proponents of eating ''disorders''), and the provision of social support to ingroup members (Brotsky and Giles 2007;Giles 2006;Riley et al 2009;Teufel et al 2013;Wooldridge et al 2014). A high proportion of eating disorder patients utilize these websites (Wilson et al 2006).…”
Section: Social Identity Theorymentioning
confidence: 99%